Social Innovations In Companies And In Social Economy Enterprises - Furmańska-Maruszak, Agnieszka; Sudolska, Agata (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper compares the way of perceiving and implementing social innovations in companies and social enterprises in Poland with those in Europe. Special attention is paid to internal social innovations, so-called workplace innovations (WPI), and the reasons and outcomes of their introduction in companies, both in Poland and in other European countries. Moreover, the paper investigates the relationship between the need for internal social innovations and positive employment relations in analyzed entities. The research findings prove that introducing innovations, including social innovations, is mainly driven by the need to improve a company’s performance. Among social innovations which both companies and social enterprises value is investment into improving employees’ work conditions. Moreover, for more than half of Polish companies and social enterprises the need for innovations is related to creating development opportunities, higher work flexibility, better social and life conditions of employees, as well as supporting employee’s reconciliation between work and family life. These reasons for introducing social innovations were also noted by both managers and employees in other European companies. The paper also shows the links between issues of internal social innovations and positive employment relationships. The presented research findings prove that positive relationships among employees are significantly and positively correlated with a broad approach to the need for introducing social innovations. Moreover, the paper points out that positive employment relations are perceived as an important outcome of workplace innovation practices in European companies.